2013
DOI: 10.3322/caac.21171
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, pathophysiology, and treatment of hot flashes in cancer

Abstract: Hot flashes are prevalent and severe symptoms that can interfere with mood, sleep, and quality of life for women and men with cancer. The purpose of this article is to review existing literature on the risk factors, pathophysiology, and treatment of hot flashes in persons with cancer. Electronic searches were conducted to identify relevant, English-language literature published through June 15, 2012. Results indicated that risk factors for hot flashes in cancer include patient-related factors (eg, age, race/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 271 publications
(313 reference statements)
0
31
0
2
Order By: Relevance
“…Fisher et al found that ~80% of women receiving tamoxifen experienced hot flashes 9. Hot flashes are sudden and transient episodes of heat and sweating with possible palpitations and anxiety 10. Their pathophysiology is unclear and appears to involve thermoregulatory and neurochemical disruptions 9.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher et al found that ~80% of women receiving tamoxifen experienced hot flashes 9. Hot flashes are sudden and transient episodes of heat and sweating with possible palpitations and anxiety 10. Their pathophysiology is unclear and appears to involve thermoregulatory and neurochemical disruptions 9.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although vasomotor symptoms (VMS) have been the focus of most intervention studies, 6, 7 they do not occur in isolation. VMS frequently co-occur with disturbed sleep and mood, fatigue, trouble remembering or concentrating, and/or sexual difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…13, 810 These co-occurring symptoms are typically not assessed or are considered secondary outcomes, with few trials specifically targeting more than one symptom. 6, 7, 11, 12 Research shows that symptoms act synergistically and that the impact of co-occurring symptoms on an individual is multiplicative rather than additive. 9, 13 Thus, addressing multiple co-occurring symptoms is vital to improving midlife women’s quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Despite missing information on the timing and type of OET and the use of menopausal symptom management strategies (pharmaceutical, nutraceutical, surgical, or alternative/ behavioral), 9 the main point of the large study by Davis et al 2 is that menopausal symptoms were prevalent and severe in long-term breast cancer survivors. This is a special population of women for whom nonhormone interventions are needed.…”
mentioning
confidence: 99%